The spirit, indigenous peoples, and social change : Maori and a Pentecostal theology of social engagement - Frost, Michael J., (Global Pentecostal and Charismatic Studies, 2018)
In The Spirit, Indigenous Peoples and Social Change Michael Frost explores a pentecostal theology of social engagement in relation to Māori in New Zealand. Pentecostalism has had an ambiguous relationship with Māori and, in particular, lacks a robust and coherent theological framework for engaging in issues of social concern. Drawing on a number of interviews with Māori pentecostal leaders and ministers, Frost explores the transformative role of pentecostal experience for Māori cultural identity, a holistic theology of mission, an indigenous prophetic emphasis, and consequent connections between pentecostalism and liberation. He thus contributes a way forward for pentecostal theologies of social change in relation to Māori, with implications for pentecostalism and indigenous peoples in the West.